2014
DOI: 10.1038/jid.2014.231
|View full text |Cite
|
Sign up to set email alerts
|

miR-330-5p Targets Tyrosinase and Induces Depigmentation

Abstract: Epidermal vascular endothelial growth factor production is required for permeability barrier homeostasis, dermal angiogenesis, and the development of epidermal hyperplasia: implications for the pathogenesis of psoriasis. Am J Pathol 173:689-99 Elias PM, Wakefield JS (2011) Therapeutic implications of a barrier-based pathogenesis of atopic dermatitis. Clin Rev Allergy Immunol 41:282-95 Friedman SJ (1987) Management of psoriasis vulgaris with a hydrocolloid occlusive dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Because our previously miRNAs array also identified significant differential expression of miR-330-5p in the skin of different coat colors of animals [18,19]. Other report indicated that keratinocytes produce miR-330-5p [27] and miR-330-5p downregulated the expression of TYR that plays a key role in pigmentation [28,29]. Whether and how miR-330-5p regulates TYR in melanocytes to regulate pigmentation is not clear.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because our previously miRNAs array also identified significant differential expression of miR-330-5p in the skin of different coat colors of animals [18,19]. Other report indicated that keratinocytes produce miR-330-5p [27] and miR-330-5p downregulated the expression of TYR that plays a key role in pigmentation [28,29]. Whether and how miR-330-5p regulates TYR in melanocytes to regulate pigmentation is not clear.…”
Section: Introductionmentioning
confidence: 94%
“…It was reported that MITF regulates gene expression [34]. To evaluate whether TYR [28] is the target gene of miR-330-5p, we measured the expression of TYR, TYRP1, TYRP2 and MITF in melanocytes treated with different exosomes. We found that the expression levels of TYR, TYRP1, TYRP2 and MITF proteins and genes were downregulated in the exosomes overexpressed with the miR-330-5p group compared with the control (Fig.…”
Section: Exosomes Carry Mir-330-5p That Regulate Melanocyte Pigmentationmentioning
confidence: 99%
“…MiRNAs can bind with partial complementarity to sequences in the 3' untranslated region (3'-UTR) of target mRNAs for the regulation of gene expression. A growing number of events have shown that miRNAs are crucial for skin homeostatic maintenance (Table 1) [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Mirna In Vitiligomentioning
confidence: 99%
“…MiRNAs have been implicated in targeting TYR or MITF, which are potentially involved in the pigmentation process, to regulate their expression levels. For example, miR-434-5p and miR-330-5p are upstream regulators of TYR expression, suggesting that these miRNAs could be used as potential therapeutic targets for pigmentation 40,41,53 .…”
Section: Mirnas Associated With Melanocyte Proliferation Differentiamentioning
confidence: 99%
“…Another miRNA that could potentially be applied to treating aberrant skin pigmentation is miR-211, which was shown to target transforming growth factor (TGF)-β receptor in an MITF-dependent fashion [ 64 ]. Others include miR-25, miR-125b, miR-137, and miR-182, all of which target MITF; miR-330-5p, which targets TYR; and miR-145, which is a key regulator of many genes in the pigmentation process, such as TYR, TRP1, and MITF [ 65 , 66 , 68 71 ]. In cell culture, it was shown that miR-155 contributed to the pathogenesis of vitiligo by downregulating multiple genes associated with melanogenesis, including suppressor of cytokine signaling 1 (SOCS1) and TRP1, and that increased levels of miR-155 contributed to development of the skin disease [ 72 ].…”
Section: Introductionmentioning
confidence: 99%